First palaeointensity data from the cryogenian and their potential implications for inner core nucleation age - Lloyd, Simon J; Biggin, Andrew J; Halls, Henry; Hill, Mimi J (Geophysical journal international, 2021)
SUMMARY The timing of inner core nucleation is a hugely significant event in Earth's evolution and has been the subject of intense debate. Some of the most recent theoretical estimates for the age of nucleation fall throughout the Neoproterozoic era; much younger than previously thought. A young inner core requires faster recent core cooling rates and a likely hotter early core; knowledge of its age would be invaluable in understanding Earth's thermal history and total energy budget. Predictions generated by numerical dynamo models need to be tested against such data, but records are currently much too sparse to constrain the event to a precise period of time. Here, we present results from 720 Ma dolerite dykes (and one sill) from the Franklin Large Igneous Province, which fall within a crucial 300 Myr gap in palaeointensity records. This study uses three independent techniques on whole rocks from 11 sites spread across High Arctic Canada and Greenland to produce virtual dipole moments ranging from 5 to 20 ZAm2 (mean 11 ZAm2); almost one order of magnitude lower than the present-day field. These weak-field results agree with recent ultralow palaeointensity data obtained from Ediacaran rocks formed ∼150 Myr later and may support that the dynamo was on the brink of collapse in the Neoproterozoic prior to a young inner core formation date.